USE OF RADIOLOGICAL DIAGNOSTIC MODALITIES IN TERTIARY CARE HOSPITAL - HOW DO THE CLINICIANS DECIDE ABOUT TYPE OF MODALITY AND CLINICIAN PERCEPTION REGARDING HAZARDS ASSOCIATED WITH RADIOLOGICAL IMAGING MODALITIES? - Ali, Azmat; Faiza Akram,; Laila Khan,; Iffat Ara, (Journal of Ayub Medical College Abbottabad, 2021)
Background: In the past few decades there is rapid advancement in technology and hence tremendous innovations in diagnostic imaging. This has increased our ability to diagnose illness and monitor response to treatment in a manner which was not previously possible. As compared to previous times, there is also more easy availability of these diagnostic imaging modalities in our hospitals. Therefore, easy and frequent availability harbour the risk of injudicious use of these tests as well. This study is conducted to know the views of consultants about it. Methods: This cross-sectional descriptive study was conducted in Ayub Medical Institute MTI from March 2021 to July 2021. The data was collected through a self-administered anonymous questionnaire. Results: A total of 250 clinicians participated in the study with 54% males. Majority of them (n=140) 56% answered that consultants on round and on duty in OPD decide special radiological investigations for the patients. Most of them (90%, n=225) were aware of radiation hazards in CT, X-rays and fluoroscopy. Conclusion: The referring physicians working at MTI ATH Abbottabad have enough basic knowledge regarding the practice of radiological modalities but were unaware of specific health hazards and radiation doses to the patients associated with the use of these imaging modalities.